Detection of Intrusions and Malware, and Vulnerability Assessment : 12th International Conference, DIMVA 2015, Milan, Italy, July 9-10, 2015, Proceedings - Almgren, Magnus; Gulisano, Vincenzo; Maggi, Federico; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 12th International Conference on Detection of Intrusions and Malware, and Vulnerability Assessment, DIMVA 2015, held in Milan, Italy, in July 2015. The 17 revised full papers presented were carefully reviewed and selected from 75 submissions. The papers are organized in topical sections on attacks, attack detection, binary analysis and mobile malware protection, social networks and large-scale attacks, Web and mobile security, and provenance and data sharing.
Keywords: Computer security; Information Systems; Systems and Data Security; e-Commerce/e-business.; Management of Computing and Information Systems